2020
DOI: 10.1080/21691401.2020.1813740
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic targeting of glycyrrhetinic acid via nanomicelles based on stearic acid-modified fenugreek gum

Abstract: This study aimed to increase the solubility of glycyrrhetinic acid (GA) in water and enhance its liver-targeting ability using self-assembling nanomicelles (NMs) based on stearic acid-modified fenugreek gum . The GA/FG-C 18 NMs were prepared by an ultrasonication dispersion method. The nanomicelles were spherical particles with a particle size of 198.61 ± 1.58 nm and a zeta potential of À30.12 ± 0.28 mV. The drug loading and encapsulation efficiency were 13.34 ± 0.24% and 80.07 ± 1.44%, respectively. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The apparent viscosity of FA-ASA-FG/MTX was higher than that of SA/MTX because FG might interpenetrate the hydrogel network, which further proves that FA-ASA-FG/MTX had a denser network structure. 29 The above results confirmed the successful preparation of drug-loaded hydrogels, and showed that FA-ASA-FG/MTX had a high complex viscosity and apparent viscosity.…”
Section: Rheological Behavior Of Fa-asa-fg/mtx and Sa/mtxsupporting
confidence: 73%
“…The apparent viscosity of FA-ASA-FG/MTX was higher than that of SA/MTX because FG might interpenetrate the hydrogel network, which further proves that FA-ASA-FG/MTX had a denser network structure. 29 The above results confirmed the successful preparation of drug-loaded hydrogels, and showed that FA-ASA-FG/MTX had a high complex viscosity and apparent viscosity.…”
Section: Rheological Behavior Of Fa-asa-fg/mtx and Sa/mtxsupporting
confidence: 73%
“…This behaviour was confirmed by the release studies (data not shown); SG was not released from the nanocarriers due to its extremely lipophilic structure (insoluble). On the other hand, GA-SLNs showed poor release due to the less lipophilic nature of GA compared to SG (<0.01 mg/mL) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%